An Upper Palaeolithic engraved human bone associated with ritualistic cannibalism. - Silvia M Bello; Rosalind Wallduck; Simon A Parfitt; Chris B Stringer (PLoS ONE)
Cut-marked and broken human bones are a recurrent feature of Magdalenian (~17-12,000 years BP, uncalibrated dates) European sites. Human remains at Gough's Cave (UK) have been modified as part of a Magdalenian mortuary ritual that combined the intensive processing of entire corpses to extract edible tissues and the modification of skulls to produce skull-cups. A human radius from Gough's Cave shows evidence of cut marks, percussion damage and human tooth marks, indicative of cannibalism, as well as a set of unusual zig-zagging incisions on the lateral side of the diaphysis. These latter incisions cannot be unambiguously associated with filleting of muscles. We compared the macro- and micro-morphological characteristics of these marks to over 300 filleting marks on human and non-human remains and to approximately 120 engraved incisions observed on two artefacts from Gough's Cave. The new macro- and micro-morphometric analyses of the marks, as well as further comparisons with French Middle Magdalenian engraved artefacts, suggest that these modifications are the result of intentional engraving. The engraved motif comfortably fits within a Magdalenian pattern of design; what is exceptional in this case, however, is the choice of raw material (human bone) and the cannibalistic context in which it was produced. The sequence of the manipulations suggests that the engraving was a purposeful component of the cannibalistic practice, implying a complex ritualistic funerary behaviour that has never before been recognized for the Palaeolithic period.